2006
DOI: 10.1177/0164027506291745
|View full text |Cite
|
Sign up to set email alerts
|

Off the Beaten Track

Abstract: Aiming to uncover the socially integrating functions of parenthood, this study focused on differences in network size between older adults with and without children, using survey data from Amsterdam (n = 661) and Berlin (n = 516). Explicit attention was paid to diversity among the childless and to their biographical pasts. The pattern of results was similar for both countries. Those who never had children had smaller networks in old age than parents, a finding partially attributable to a more limited supply of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…These results are consistent with those of other studies which have found that childless men and women are less likely than parents to interact with relatives [5,13], that they have networks of limited support potential [13], but that they do not compensate for their lack of contact with relatives by extended non-kin networks [5,11,12]. However, a definite conclusion about the differences in the social networks between the childless group and the parental group cannot be drawn given that the questionnaire did not contain questions about the number of friends or relatives present and thereby not about the size of the social networks.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with those of other studies which have found that childless men and women are less likely than parents to interact with relatives [5,13], that they have networks of limited support potential [13], but that they do not compensate for their lack of contact with relatives by extended non-kin networks [5,11,12]. However, a definite conclusion about the differences in the social networks between the childless group and the parental group cannot be drawn given that the questionnaire did not contain questions about the number of friends or relatives present and thereby not about the size of the social networks.…”
Section: Discussionsupporting
confidence: 93%
“…The studies showed that childless elderly men and women have smaller social networks [12,13], they are less likely to interact with relatives and more likely to have networks of limited support potential [14] than elderly men and women who are parents. The smaller networks are in part attributable to the lack of children and grandchildren, but there is no evidence that childless individuals have sought to increase social contacts or to extend non-kin networks to compensate for their childlessness [12,13]. However, Keith [6] and Wenger [15] found no differences in social networks and support between childless individuals and parents.…”
Section: Introductionmentioning
confidence: 99%
“…Being widowed and without children has also been found to have more negative effects on health and health behaviors than being widowed with children (Dykstra et al, 2006). Being widowed and without children has also been found to have more negative effects on health and health behaviors than being widowed with children (Dykstra et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…As Chodorow (1978) has argued, men tend to rely on their spouses for support, whereas women are socialized to have more complex affective needs in which an exclusive relationship with a spouse is not enough. Children serve as bridges to new social circles for their parents through involvements at daycare, school, clubs, sports, and the local community (Dykstra 2006;Furstenberg 2005). In this paper we focus on social integration as a subjective experience.…”
Section: Introductionmentioning
confidence: 99%